Savoirs tactiques et expertises - Aurore Viard-Crétat (Revue d'anthropologie des connaissances)
The advent of the notion of ownership in the development aid sector has brought with it a broad array of norms and of capacity-building measures to support and control practices. On the basis of an ethnographical study of the Cameroonian application process for the World Bank’s Redd+ forest programme, this article analyses what is technically at stake in these standardisation and learning processes. The expertise involved is to a large extent a matter of tactical knowledge, of networking and of ad hoc alliances. If this dynamic empowers in a certain way the Cameroonian actors, it extends at the same time the situation of dependent extraversion by confining this power of action within the scope of the programme. This study finally highlights some of the causes of Redd+ facility’s political success, and more broadly, of the cycles of enthusiasm/disillusion which regularly renew international conservation and development policies around new approaches.